THE PFAR-BASED FLIPPED CLASSROOM AT ELEMENTARY SCHOOL: STUDENTS’ VOCABULARY MASTERY - Adin Fauzi; Dinda Saroh Wahdati; Fu’ad Sholikhi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Vocabulary mastery is essential to help students learn English. However, many elementary students struggle with having sufficient vocabulary. This classroom action research aims to improve elementary students' vocabulary mastery through the PFAR-based flipped classroom. PFAR, which stands for Plan, Flip, Assess, and Reflect, is a recent development of flipped classroom for teaching English to young learners. The participants of this study included 15 grade VI students from an Islamic elementary school. The data were collected using tests, observations, and interviews. The findings revealed that the PFAR-based flipped classroom enhanced the students' vocabulary mastery. This improvement was made possible by active learning during vocabulary lessons. The students learned vocabulary through videos, pictures, and academic games, both online and in face-to-face classes. The results of the tests showed that the students were able to achieve the learning objectives, namely (1) understanding the meaning of certain vocabulary; (2) writing certain vocabulary with correct spelling; and (3) applying certain vocabulary in simple sentences. All the students yielded a mean score of more than 70 on five vocabulary tests. In addition, they became more active during the lessons and confirmed that the entire learning process was more attractive. All of this evidence suggests that this research was successful in improving students' vocabulary mastery.